2016
DOI: 10.1016/j.cub.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Annual 10-Month Aerial Life Phase in the Common Swift Apus apus

Abstract: The common swift (Apus apus) is adapted to an aerial lifestyle, where food and nest material are captured in the air. Observations have prompted scientists to hypothesize that swifts stay airborne for their entire non-breeding period [1, 2], including migration into sub-Saharan Africa [3-5]. It is mainly juvenile common swifts that occasionally roost in trees or buildings before autumn migration when weather is bad [1, 6]. In contrast, the North American chimney swift (Chaetura pelagica) and Vaux's swift (C. v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 19 publications
(25 reference statements)
5
101
0
Order By: Relevance
“…Assuming that the birds never spent the night horizontal on land, these periods of low activity might reflect an increase in the time spent soaring and gliding, perhaps related to seasonal changes in atmospheric conditions. In a similar study, Hedenströ m et al [12] found that common swifts fly throughout more than 99% of the non-breeding period, with some individuals remaining in flight for up to 300 days. Interestingly, during the rare periods when the birds landed, they roosted vertically or horizontally.…”
Section: Apodiformes (Swifts and Hummingbirds) 221 Swiftsmentioning
confidence: 96%
See 2 more Smart Citations
“…Assuming that the birds never spent the night horizontal on land, these periods of low activity might reflect an increase in the time spent soaring and gliding, perhaps related to seasonal changes in atmospheric conditions. In a similar study, Hedenströ m et al [12] found that common swifts fly throughout more than 99% of the non-breeding period, with some individuals remaining in flight for up to 300 days. Interestingly, during the rare periods when the birds landed, they roosted vertically or horizontally.…”
Section: Apodiformes (Swifts and Hummingbirds) 221 Swiftsmentioning
confidence: 96%
“…Satellite and GPS tags are shrinking in size and weight making it possible to track smaller species with this technology [9]. Accelerometers are providing insight into the flight behaviour of both large [8,10] and small birds [11,12]. Geolocators, small devices that derive a bird's location on the globe by detecting changes in the timing of sunrise and sunset, are detecting long-distance flights in birds as small as 12 g [13].…”
Section: Non-stop Fliersmentioning
confidence: 99%
See 1 more Smart Citation
“…Logging of accelerometer data has been used for three main purposes in studies of animal behaviour—(1) for classifying behaviour and mode of locomotion and flight, (2) for estimating energy demands (these two aspects have been reviewed by Brown et al 2013) and, most recently, (3) for recording actograms of individuals in order to analyse daily and annual activity and flight patterns in bird migration. The latter has recently been made possible for small migratory birds (Liechti et al 2013; Bäckman et al 2016; Hedenström et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Tracking of individuals can detail the timing of specific behaviours (e.g. nocturnal roosting of swifts exclusively during the breeding season [91]) and physiology (e.g. sleep [92]).…”
Section: (B) Ecologymentioning
confidence: 99%